Spin currents during ultrafast demagnetization of ferromagnetic bilayers. (17th August 2017) - Eschenlohr, A; Persichetti, L; Kachel, T; Gabureac, M; Gambardella, P; Stamm, C
Abstract: Ultrafast spin currents induced by femtosecond laser excitation of ferromagnetic metals have been found to contribute to sub-picosecond demagnetization, and to cause a transient enhancement of the magnetization of the bottom Fe layer in a Ni/Ru/Fe layered structure. We analyze the ultrafast magnetization dynamics in such layered structures by element- and femtosecond time-resolved x-ray magnetic circular dichroism, for different Ni and Fe layer thicknesses, Ru and Ta interlayers, and by varying the pump laser fluence. While we do not observe the transient enhancement of the magnetization in Ni/Ru/Fe discovered previously, we do find a reduced demagnetization of the Fe layer compared to a Ni/Ta/Fe layered structure. In the latter, the spin-scattering Ta layer suppresses spin currents from the Ni layer into Fe, consistent with previous results. Any spin current arriving in the lower Fe layer will counteract other, local demagnetization mechanisms such as phonon-mediated spin-flip scattering. We find by increasing the Ni and Fe layer thicknesses in Ni/Ru/Fe a decreasing effect of spin currents on the buried Fe layer, consistent with a mean free path of the laser-induced spin currents of just a few nm. Our results suggest that in order to utilize ultrafast spin currents in an efficient manner, the sample design has to be optimized with these considerations in mind, and further studies clarifying the role of interfaces in the employed layered structures are needed.